FILOSOFI PERBANKAN SYARIAH: ANTARA IDEALISME DAN PRAGMATISME - Abdul Rasyid; Nurizal Ismail (Ijtihad, 2020)
Islamic banks are the financial institutions that carry out their activities based on sharia principles. Elimination of interest in the Islamic banking system is one of the parts of the element governed by the Shari’ah. As an Islamic business entity, profit is not solely the main objective of Islamic banks but also other values such as honesty, social justice (equity), and fairness (equity) as they are have been established in the Qur’an and Sunnah. Therefore, Islamic banks, besides looking for profits, are also expected to contribute to improving the welfare and economic level of the people. This is the underlying philosophy that distinguishes it from conventional banks. However, in practice, the concept does not look optimally implemented. Islamic banks, as if carried away, focused on seeking profits by ignoring the underlying philosophy. This can be seen from the various products offered, which are dominated by Murabaha products. Does the basic philosophy of Islamic banking have to be maintained like an idealized concept that is doctrines or should it be modified with a more pragmatic approach? This paper tries to analyze the philosophy of Islamic banking in terms of theory and practice in real terms in sharia banking activities that have been carried out so far.